Effectiveness and safety of vedolizumab for maintenance treatment in inflammatory bowel disease—The Israeli real world experience. Issue 1 (January 2019) - Kopylov, Uri; Avni-Biron, Irit; Ron, Yulia; Koslowsky, Benjamin; Waterman, Matti; Daher, Saleh; Ungar, Bella; Schwartz, Doron; Zittan, Eran; Openhaim, Michal; Yanai, Henit; Maharshak, Nitsan; et al.
Abstract: Introduction: Several real-world experience (RWE) studies with vedolizumab (VDZ) for induction of remission in inflammatory bowel diseases (IBD) have been published; however, long-term RWE data is scarce. Aims: To describe the effectiveness and safety of VDZ in maintenance treatment of IBD. Methods: A multicenter retrospective national study. The primary outcome of was clinical response at week 52; main secondary aims included clinical remission at week 52, rates of secondary loss of response and treatment discontinuation. Results: We included 193 (133—CD; 60—UC) patients from 9 Israeli IBD centers. At week 52, response was observed in 62/133 (46.7%) CD patients, including 28 (21%) in clinical remission; 71 (53.3%) discontinued treatment or did not respond. For UC, response at week 52 was observed in 27/60 (45%), including 20 (33%) in clinical remission; 33 (55%) discontinued treatment or did not respond. Secondary non-response by week 52 occurred in 19.4% and 23.5% of week 14 responders in CD and UC, respectively. Week 14 response was associated with treatment continuation at week 52: no predictors of secondary loss of response were identified. Summary: VDZ is safe and effective for maintenance of response and remission in IBD; week 14 response is positively associated with long-term response in both UC and CD.